1999
DOI: 10.1192/apt.5.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Psychodynamic interpersonal therapy

Abstract: The dramatic development of cognitive–behavioural therapy (CBT) over the past 30 years, with associated high-quality research into the evaluation of its treatment effects, is to be welcomed and applauded. This form of therapy is now a recognised psychological treatment of choice for a wide variety of psychological disorders. The role of cognitive processes in the development and prolongation of psychological symptoms has been studied, and resulted in the development of coherent and effective treatment models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…In terms of research, the PIT is one of the small numbers of non‐cognitive behavioural therapies for which there is an evidence base drawing on trials methodology. The model has been the subject of a programme of research which has demonstrated the following: (1) efficacy for people who self‐harm (Guthrie et al , 2001); (2) reduction in healthcare costs for people with chronic non‐psychotic psychiatric problems (Guthrie, Moorey, Barker, Margison, & McGrath, 1998; Guthrie et al , 1999); (3) palliative effect for people with irritable bowel syndrome and chronic dyspepsia (Guthrie, Creed, Dawson, & Tomenson, 1991; Hamilton et al , 2000); and (4) broadly equivalent outcomes with cognitive behavioural therapy for people presenting with depression (Shapiro et al , 1994).…”
Section: Psychodynamic‐interpersonal Psychotherapymentioning
confidence: 99%
“…In terms of research, the PIT is one of the small numbers of non‐cognitive behavioural therapies for which there is an evidence base drawing on trials methodology. The model has been the subject of a programme of research which has demonstrated the following: (1) efficacy for people who self‐harm (Guthrie et al , 2001); (2) reduction in healthcare costs for people with chronic non‐psychotic psychiatric problems (Guthrie, Moorey, Barker, Margison, & McGrath, 1998; Guthrie et al , 1999); (3) palliative effect for people with irritable bowel syndrome and chronic dyspepsia (Guthrie, Creed, Dawson, & Tomenson, 1991; Hamilton et al , 2000); and (4) broadly equivalent outcomes with cognitive behavioural therapy for people presenting with depression (Shapiro et al , 1994).…”
Section: Psychodynamic‐interpersonal Psychotherapymentioning
confidence: 99%
“…In a later paper, Guthrie (1999) gives more detail about the treatment and characterizes it as "psychodynamic interpersonal therapy." It focuses on identifying interpersonal difficulties in the patient's life that are responsible for either precipitating or maintaining symptoms.…”
Section: Brief Psychodynamic Psychotherapymentioning
confidence: 99%
“…The Conversational Model is an integrative model of therapy that combines psychodynamic, humanistic, and interpersonal theory and techniques. This integration enables the model to be clearly identified as a distinct model of therapy (Guthrie 1999). However, the underpinning ‘style’ or ‘fundamental stance’ of the model is of equal if not greater importance than the technical interventions that are used in the model.…”
Section: Introductionmentioning
confidence: 99%